2019
DOI: 10.3390/ijerph16244883
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bacterial Community and Function in Paddy Soil Profile around Antimony Mine and Its Response to Antimony and Arsenic Contamination

Abstract: Research of bacterial communities and metabolism potential of paddy soils contaminated by antimony (Sb) and arsenic (As) are vital to acquire understanding for their bioremediation. Here, the relative abundance of Sb and As metabolism genes, the diversity and composition of the bacterial community, and the influences of geochemical properties and the bacterial community and metabolism potential have been researched by Tax4Fun2 prediction and high-throughput sequencing. LEfSe (linear discriminant analysis effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The V3-V4 hypervariable regions of the bacterial 16S rRNA gene were amplified with primers 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′) by a thermocycler PCR system (GeneAmp 9700, ABI, USA) 21 . The PCRs were conducted as follows: 3 min of denaturation at 95 °C, 27 cycles of 30 s at 95 °C, 30 s for annealing at 55 °C, and 45 s for elongation at 72 °C, and a final extension at 72 °C for 10 min 22 . The resulting PCR products were extracted from a 2% agarose gel and further purified using an AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The V3-V4 hypervariable regions of the bacterial 16S rRNA gene were amplified with primers 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′) by a thermocycler PCR system (GeneAmp 9700, ABI, USA) 21 . The PCRs were conducted as follows: 3 min of denaturation at 95 °C, 27 cycles of 30 s at 95 °C, 30 s for annealing at 55 °C, and 45 s for elongation at 72 °C, and a final extension at 72 °C for 10 min 22 . The resulting PCR products were extracted from a 2% agarose gel and further purified using an AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The 20 taxa with the highest abundance were shown, while the other taxa were the sum and represented as “other”. The red star indicates known 6:2 FTSA degraders, , while the black triangle indicates known 6:2 FTOH degraders …”
Section: Resultsmentioning
confidence: 99%
“…Within a microbial community, diverse and multiple species can perform similar catabolic functions that affect the microbial community structure over time or in response to stimuli. To evaluate the functional capacity of the soil microbiome in sandy soil and rhizosphere sandy soil that received different treatments, Tax4Fun2 was used to predict functional features based on the 16S rRNA gene sequencing data. Our previous study reported desulfonation and defluorination enzymes involved in 6:2 FTSA biodegradation by RHA1 . So, the analysis was focused on these known desulfonation and defluorination enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…RDA describes the proportions of the variation of a dependent variable in the total variations of the dependent variables that are caused by the linear relationships between the dependent variables and typical variables. The RDA analysis of the relationships of the selected indices between soil and S. oleracea was performed using the ape package, vegan package, psych package, and reshape2 package in the R language (3.6.0) [25].…”
Section: Evaluation Methods For Soil and S Oleracea 241 Evaluation Of Redundancy Analysismentioning
confidence: 99%